Differentiating Depression from Apathy in Chronic Kidney Disease: A Prospective Study - R. Schoenfeld; K. Mueller; M. Girndt; P. Mohr; A. Malecki; S. Schneider; J.T. Kielstein; K. Jaeger (Journal of Depression And Therapy, 2017)
Background. Emotional deterioration is frequently found in patients with chronic kidney disease, but some patients are affected by depressed mood without fulfilling the criteria of a depressive disorder. Those patients might rather suffer from an apathy symptom. Apathy as a symptom of a medical disease is accompanied by loss of motivation and interest, cognitive impairments, and emotional distress. Our study tested how groups of apathetic and depressed chronic kidney disease patients responded to a single haemodialysis session on measures of mood. Methods. 21 haemodialysis patients were assigned to subgroups (depressed, apathetic only, without depression and apathy) according to clinical relevant cut-offs. Sensitive questionnaires were administered to monitor mood state in general and mood changes before and after a single haemodialysis session in the chronic kidney disease patients. The results were compared to 20 age-matched healthy controls receiving no treatment. Results. Fortheen dialysis patients had eighter apathy or depressen and seven had neighter apathy nor depression. Mood state was seriously affected in all haemodialysis patients with depressed patients showing the largest effect compared to healthy controls. Patients with apathy and patients without apathy and depression were comparable in their mood state. We observed a positive mood change after the haemodialysis only in patients without apathy and depression. Their mood state improved significantly and reached nearly the level of healthy controls. Conclusions. The absence of a short-term mood change in apathetic dialysis patients makes them comparable to dialysis patients with depression. We argue that apathetic patients lack the probable mood brightening effect of the haemodialysis. The lack of emotional improvement by dialysis sessions could also lead to decreased adherence of the patients. Hence, apathy seems to be a serious symptom in chronic kidney disease that is worth to be considered at least in the diagnostic process. Accompanying psychotherapeutic care for these patients would be desirable
Keywords: chronic kidney disease